ENHANCING MULTICULTURAL AWARENESS IN HIGH SCHOOL SOCIOLOGY THROUGH DIORAMA-BASED CULTURALLY RESPONSIVE TEACHING - Tresa Febrianita; Elly Malihah Setiadi; Wilodati Wilodati (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the effect of diorama-based Culturally Responsive Teaching (CRT) on the enhancement of high school students' multicultural awareness. It also compares the increase in awareness between students who participated in diorama-based learning and those who used cultural-themed posters.Methodology – A quasi-experimental non-equivalent control group design was employed involving two intact classes of sociology students (n=76) at SMAN 1 Ciparay. The experimental group received diorama-based CRT integrated with Project-Based Learning, while the control group utilized thematic posters. Data were collected using validated pre-test and post-test questionnaires measuring four indicators of multicultural awareness. The analysis utilized gain scores, the Shapiro-Wilk normality test, and the Mann-Whitney U non-parametric test.Findings – Descriptively, the experimental group's average score increased from 113 to 117 (average gain = 3.16), whereas the control group's average score increased from 109 to 111 (average gain = 1.68). The Wilcoxon test confirmed a significant internal improvement within the experimental group (p < 0.001). Furthermore, the Mann-Whitney U test demonstrated a statistically significant difference in gain scores between the two groups (p = 0.022, r = 0.262). Commitment to social justice and empathy for other groups exhibited the most prominent improvement.Contribution – This research enriches the study of CRT implementation in sociology education, offering concrete pedagogical alternatives for pluralistic societies like Indonesia. The findings highlight that structured, project-based diorama activities can positively influence students' multicultural awareness and support experiential learning strategies in the curriculum.